A closed-loop sustainable scheme for silver recovery from water by reusable thiol-grafted graphene oxide. (10th July 2021) - Zhang, Zhiyong; Kuang, Yue; Lin, Yan; Wu, Deyi
Abstract: Two-dimensional graphene oxide was modified with mercaptoethylamine and then treated with sodium dithionite to produce a 3D thiol-grafted graphene oxide (TGO) composite, which was investigated for the highly selective recovery of silver ions from water. Scanning electron microscopy, powder X-ray diffraction, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy were used to characterize the material before and after Ag + adsorption. Batch adsorption experiments were carried out as a function of the initial Ag + concentration, agitation time, temperature, and pH. The maximum adsorptive capacity of Ag + by TGO, obtained from the Langmuir model, which fit the isotherm data well, reached 134.1 mg/g at 25 °C and a pH of 5.0. In addition, the adsorption was an endothermic process, and the adsorption kinetics followed the pseudo-second-order model. TGO was highly selective for Ag + ; the selectivity factor of Ag + reached 445 compared to Cu 2+ ions and exceeded 1900 compared to Zn 2+, Mg 2+, Ca 2+, Na +, and K + ions. The adsorption of Ag + on TGO induced the release of H +, and increased adsorption with increasing pH was observed. The adsorbed Ag + can be proportionally desorbed using 1% HNO3 . The reusability of TGO was confirmed by five cycles of adsorption-desorption-regeneration. The adsorption column studies indicated that TGO was stable in water and can be used as a filtering material for Ag + recovery. The binding mechanism of Ag + by TGO was proposed as the coordination of Ag + with the sulfur atom of the mercapto groups attached to TGO followed by the reduction of Ag + to Ag 0 . Highlights: Thiol-grafted graphene oxide (TGO) is prepared by loading mercaptoethylamine on GO. The maximum adsorption capacity of Ag + on TGO attained 134.1 mg/g at 25 °C at pH 5. The Ag + adsorption increased with increasing temperature and pH. Adsorption mechanism is the coordination of Ag + with sulfur atom of thiol on TGO. High selectivity and good reusability after desorption/regeneration were confirmed.